Errors that occur during the production of fabrics for rest and recreation: An example from industrial practice - Đorđević Suzana; Gebes Ferhan; Stojanović Nikola; Antić Slađana (Tekstilna industrija)
Certain negative phenomena that occur when weaving on a shuttle loom are described and analyzed in this paper. The manufactured fabric is used to produce different types of items for rest and relaxation, e.g. garden and home swings, then swings and baby carriers, etc. The fabric is made on a weaving loom with a shuttle, from the company "Textima". The analysis found that, during weaving, errors occur that originate from oil, thicker threads, burls, knots, fuzz, hairs, etc. dominate. These errors can be easily eliminated by careful work and timely interventions on the loom itself. The number of warp and weft breaks is mostly within normal limits and depends on the quality of the yarns used and the quality of their preparation. Inspection of the finished fabric by trained and skilled workers confirms the errors that occur during weaving.